Green Nanotechnology and Nanomaterials for Sustainable Development Goals (SDGs) - Yunasar; Muttaqin; Sri Indah Setiyaningsih; Abd Mujahid Hamdan (Bansigom Na Publisher, 2025)
Green nanotechnology and nanomaterials present innovative solutions to address global sustainability challenges. Their applications span renewable energy, water purification, agriculture, and healthcare, contributing to the achievement of Sustainable Development Goals (SDGs). This article explores the principles of green nanotechnology, methodologies for sustainable nanomaterials synthesis, and their impact on SDGs. Experimental results highlight the effectiveness of green nanomaterials in enhancing energy efficiency and environmental remediation. The findings underscore the transformative potential of nanotechnology in fostering sustainable development.